Why urbanisation and health? - Lenzi, Andrea (Acta Biomedica Atenei Parmensis, 2019)
In 2007 more than 50% of the world’s population were living in metropolitan cities, which was the first time in history that the urban population level had risen above 50%.The urban population have grown ever since and will continue to do so according WHO estimates. By 2030it has been estimated that 6 people out of 10 will live in urban agglomerates and an estimate of 70% of the inhabitants will be living in urban environments by 2050. ...